Identify and Analyze Various Types of English Syllables - Divo Pratama Pasaribu; Muhammad Faisal Hajmi Bin Nasir; Najla Regar; Nadila Adelia Putri; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research presents an in-depth analysis of various types of English syllables, including closed, open, vowel-consonant-e, vowel team, r-controlled, and consonant-le syllables. Each type of syllable has unique characteristics that contribute to the structure and pronunciation of words in English. Closed syllables produce short vowel sounds due to the ending consonant, while open syllables result in long vowel sounds due to the ending vowel. Vowel-consonant-e syllables involve a vowel followed by a consonant and a silent 'e,' which lengthens the vowel sound. Vowel team syllables consist of two vowels that together produce a single vowel sound, while r-controlled syllables involve a vowel followed by the letter 'r,' which alters the vowel sound. Consonant-le syllables, typically found at the end of words, provide a distinctive rhythm and flow. This study demonstrates that a theoretical understanding of syllable types has significant implications for phonics instruction and language education. Phonics instruction based on syllable patterns can enhance reading fluency and spelling proficiency. The analysis also reveals phonological diversity in English, reflecting the language's adaptability and complexity. Understanding syllable structures also provides insights into how the brain processes language, which is crucial for developing effective language teaching strategies.